G146 A systematic review of mental health outcomes in young people following sexual assault. (27th April 2015) - MacGregor, KE; Villalta, L; Clarke, V; Viner, RM; Kramer, T; Khadr, SN
Abstract : Aims: Sexual assault peaks in mid-to late adolescence but its sequelae among this age group are not well understood. This systematic review aimed to describe mental health outcomes in young people following sexual assault. Methods: Two reviewers searched Medline, Embase, CINAHL, OpenGrey and PsycINFO databases independently, screening publications from 1990 to 30 th October 2013. Inclusion criteria : longitudinal studies, systematic reviews and meta-analyses in English with ≥50% participants aged 10–24 years; baseline mental health assessment conducted prior to or <8 weeks post-assault with follow-up ≥3 months later, and within three years of index assault. Study selection, data extraction and quality assessment were performed independently, with any differences resolved by a third person. Quality assessment used the Newcastle-Ottawa Scale. Results: 3, 758 titles and abstracts were screened after excluding duplicates, with 494 papers examined in full. Five cohort studies met inclusion criteria (sample size 64–294; mean age 13–26 years; duration of follow-up 3–12 months post-assault). Three studies examined rates of Post-Traumatic Stress Disorder (PTSD), reporting rates of 88%–94% within a month of assault, 47%–71% by 3 months and 10.5%–65% by 12 months post-assault. Only one study measured rates of Depressive Disorder, reporting rates of 35% 6 months post-assault. A study assessing anxiety disorders 6 months post-assault found that 11% had Generalised Anxiety, 16%, Panic Disorder, 44%, Social Phobia, 41%, Specific Phobia and 56%, Agoraphobia. Longitudinal studies evaluating post-traumatic (n = 3), depressive (n = 2) or anxiety symptom scores (n = 1) all reported reduced symptoms over 6–12 months post-assault. Limitations: Small sample sizes, and heterogeneity of study populations, measures used and follow-up schedules. Conclusion: Psychopathology is common following sexual assault in young people. Most studies reviewed observed reduced rates of mental health disorders and reduced symptom scores over time but there is a paucity of longitudinal research in this area. Large scale, good quality studies are needed to characterise the nature and course of mental health difficulties experienced by adolescent sexual assault victims over time, in order to allow for better targeting of resources for these individuals.